Innovator networks and regional knowledge base - Uwe Cantner; Andreas Meder; Anne ter Wal (Friedrich Schiller University Jena and Max Planck Institute of Economics, 2008)
This paper concerns the regional innovation system approach. It deals with the characteristics of three regional systems, Northern Hesse, Alpes-Maritime and Jena, and focusses on each regional network of innovators. In this context the importance of the size and homogeneity of a regional pool of knowledge spillovers for those networks is analyzed. We find evidence that an increasing regional knowledge base in combination with an increasing homogeneity of this knowledge base enhances the knowledge ows and the incentives for actors to interact with each other.
Keywords: O31; P25; Q55; 330; Cooperation; innovator networks; complementarity of knowledge; interaction structure; Innovation; Business Network; Forschungskooperation; Region; Räumliche Interaktion; Wissenstransfer; Spillover-Effekt; Vergleich; Hessen (Nord); Alpes-Maritimes (Dep.); Jena (Region)